ASPP2κ Is Expressed In Human Colorectal Carcinoma And Promotes Chemotherapy Resistance And Tumorigenesis - Ingmar Rieger (Frontiers Media S.A., 2021)
Alternative splicing is a common physiologic mechanism to generate numerous distinct gene products from one gene locus, which can result in unique gene products with differing important functional outcomes depending on cell context. Aberrant alternative splicing is a hallmark of cancer that can contribute to oncogenesis and aggressiveness of the disease as well as resistance to therapy. However, aberrant splicing might also result in novel targets for cancer therapy. ASPP2 is a haplo-insufficient tumor suppressor, that functions through both p53-dependent as well as p53-independent mechanisms to enhance cell death after stress. Interestingly, the common human tumor TP53 mutations result in a loss of the binding sites to ASPP2, leading to impaired induction of apoptosis. Vice versa, attenuation of ASPP2 has been described to be associated with high-risk disease, therapy failure and poor clinical outcome especially in tumors harboring the TP53 wildtype (WT) isoform. We have recently identified a novel, dominant-negative splicing variant of ASPP2, named ASPP2κ, with oncogenic potential. Exon-skipping results in a reading-frame shift with a premature translation stop, omitting most of the ASPP2 C-terminus - which harbors the p53-binding domain. Consequently, the ASPP2-p53 interaction is abrogated, which in part impacts on oncogenesis, aggressiveness of disease and response to therapy. Since ASPP2κ has been shown in hematologic malignancies to promote tumorigenesis, we further wished to determine if aberrant ASPP2κ expression plays a role in human solid tumors. In this report, we find that ASPP2κ is frequently expressed in human colorectal tumors (CRC). Using ASPP2κ overexpressing and interference CRC models, we demonstrate a functional role of ASPP2κ in contributing to oncogenesis and resistance to therapy in CRC by 1) enhancing proliferation, 2) promoting cell migration and, 3) conferring resistance to chemotherapy induced apoptosis. Our findings have far-reaching consequences for future diagnostic and therapeutic strategies for ASPP2κ expressing colorectal cancer patients and provide proof-of-principle to further explore ASPP2κ as potential predictive marker and target for therapy in clinical trials.